Changes in the root microbiome of four plant species with different mycorrhizal types across a nitrogen deposition gradient in ombrotrophic bogs. (June 2022) - Boeraeve, Margaux; Kohout, Petr; Ceulemans, Tobias; Cajthaml, Tomas; Tedersoo, Leho; Jacquemyn, Hans
Abstract: Anthropogenic activities have severely altered biogeochemical cycles with far-reaching consequences for biodiversity and ecosystem functioning. The use of artificial fertilizers, increased legume cultivation and fossil fuel combustion has resulted in a twofold increase of inorganic nitrogen input in natural ecosystems worldwide, often with considerable negative effects on plant and microbial communities. However, not all ecosystems are as sensitive to increased nitrogen deposition and effects may vary among ecological and taxonomic groups. Here, we studied how increasing nitrogen deposition affected soil and root-associated microbial communities of plants growing in ombrotrophic bogs. We specifically tested the hypothesis that microbiomes of plants with different mycorrhizal types respond differently to increased nitrogen deposition. We sampled soil and the roots of three plant species of different mycorrhizal types – arbuscular mycorrhizal ( Molinia caerulea), ectomycorrhizal ( Betula pubescens), ericoid mycorrhizal ( Vaccinium oxycoccos) – and a non-mycorrhizal plant species ( Eriophorum vaginatum) along a nitrogen deposition gradient in Europe (5–30 kg N ha −1 year −1 ). For each sample, the fungal and bacterial biomass and community composition were assessed and related to current levels of nitrogen deposition. In general, we found that fungi were more strongly affected by increased nitrogen deposition than bacteria. Fungal biomass, richness and diversity significantly decreased with increasing nitrogen deposition while bacterial biomass, richness and diversity was indifferent. OTU richness, diversity or community composition of ericoid mycorrhizal fungi did not change with increasing nitrogen deposition, while ectomycorrhizal fungal OTU richness and diversity significantly declined and community composition changed. We did not find an increase in arbuscular mycorrhizal fungi biomass along this gradient, despite the strong increase in abundance of the arbuscular mycorrhizal plant M. caerulea with increasing nitrogen deposition. We conclude that atmospheric nitrogen deposition has stronger effects on fungal than on bacterial communities in ombrotrophic bogs and that fungal guilds differ in their response. Highlights: Fungal biomass and diversity decreased with increasing N deposition (5–30 kg N ha −1 year −1 ). Bacterial communities were not related to increased N deposition. N deposition effects were strongest on EcM fungi while ErM fungi were unresponsive. AMF biomass was not related to N deposition but to pH and moisture.